Los mamíferos silvestres de la zona lacustre de Xochimilco - Jiménez Gutiérrez, Alan Roy (Universidad Autónoma Metropolitana, 2016)
From literature review, consult a scientific and fieldwork collections, updated the list of wild mammals of the Lake of Xochimilco in Mexico City. 17 species were recorded, of which three species reported in literature, between 1953 and 1980 are added, but no longer were found in the field. That includes an annotated list, among others, data on the biology of the species and in some cases additional comments from the locals taxonomic, keys were developed for the identification of mammals in the area, as well. With field data and collections, trends discussed in the distribution of mammals of ZLX, including sampling effort (87%), the wealth and diversity, similarity between areas and types of vegetation, and affinities of the latter by multivariate analysis. Overall, over 70% of wild mammal fauna in the ZLX itself mainly distributed over portions predominantly secondary vegetation and agricultural land, where high diversities were recorded, excelling abundance of Northern pigmy mouse (Baiomys taylori). Instead, the subaquatic vegetation, which is the most representative of place and dominated mainly by cattails, showed low richness and diversity. However, in this vegetation was found a great abundance of Western harvest mouse (Reithrodontomys megalotis). Important addition record for the rice rat (Oryzomys fulgens), of which few records for the Valley of Mexico is available; therefore broadleaf cattails of ZLX represent very important habitat, especially for mammals. In general, wild mammals that inhabit the ZLX of tolerated and have to be adapted to the changes suffered by it, although main factor habitat loss by urbanization is the threatening of these species, particularly those found in subaquatic vegetation.; A partir de revisión bibliográfica, consulta a colecciones científicas y de trabajo de campo, se actualizó la lista de los mamíferos silvestres de la Zona Lacustre de Xochimilco (ZLX) en la Ciudad de México. Se registraron 17 especies, a las que se agregan tres especies reportadas en literatura especializada, entre 1953 y 1980, pero que no fueron halladas en el campo. Se elaboraron claves taxonómicas para la identificación de los mamíferos en la zona, una lista comentada. Se analizan la riqueza y diversidad de mamíferos de la ZLX, el esfuerzo de muestreo (87% de las especies registradas), así como la similitud entre áreas y tipos de vegetación, con base en su mastofauna compartida, además de las afinidades de ésta última por medio análisis multivariados. En general, más del 70% de la mastofauna silvestre en la ZLX se distribuye principalmente sobre las porciones con predominio de vegetación secundaria y los terrenos de cultivo, en los que se registraron diversidades altas, sobresaliendo la abundancia del ratón pigmeo (Baiomys taylori). En cambio, la vegetación subacuática, que es la más representativa del lugar y está dominada principalmente por tulares, mostró baja riqueza y diversidad. Sin embargo, ahí se encontró una gran abundancia del ratón moreno (Reithrodontomys megalotis), además de un importante registro para la rata arrocera (Oryzomys fulgens), de la cual se tienen escasos registros para el Valle de México; por ende, los tulares de la ZLX representan un hábitat de suma importancia, principalmente para los micromamíferos. En general, los mamíferos silvestres que habitan en la ZLX han tolerado y se han adaptado a los cambios sufridos por la misma, aunque la pérdida de hábitat por urbanización es el principal factor que pone en riesgo a estas especies, sobre todo a las que se encuentran en los tulares.